EFL Students' Perception on the Use of Voice Note to Reduce Their Speaking Anxiety - Hapsari, Audrey Ayu; Inayati, Dian; Wardani, Sri (JET (Journal of English Teaching), 2022)
The COVID-19 outbreak has forced our education process into online learning. Unfortunately, the suddenness has left both teachers and students unprepared, causing students to experience some degree of anxiety, particularly in foreign language speaking skills. This study aims to investigate students’ perception of voice notes to reduce students’ speaking anxiety. This study employed a quantitative approach with a survey study and used a questionnaire as the instrument. The participants of this study were tenth-grade students of SMAN 1 Malang who took extra English class as their cross-interest subject in high school. This study showed positive responses regarding using voice notes in a speaking activity conducted in ELT class as students thought it could reduce their speaking anxiety. Voice note then provides a new learning media that is less stressful and pressuring on ELT in an online setting.